Emancipatory Education and Youth Engagement in Brazil: A Case Study Bridging the Theory and Practice of Education for Social Transformation - Veriene Melo (MDPI AG, 2019)
Actualizing education beyond the scope of traditional schooling and incorporating elements of critical pedagogy and social transformation are essential for efforts aiming to reduce inequalities and enhance the livelihoods of excluded populations. This article examines emancipatory education through a Freirean lens by considering its dimensions of critical pedagogy, both in practice and in theory. Drawing from a case study of an NGO-led initiative enabling hundreds of young people from the favelas of Rio de Janeiro to formulate and implement their own ideas for social action, the article examines the links between the program’s objectives and practices and the aspects of the negotiated curriculum, problem-posing education, dialogical learning, and praxis that form the theoretical underpinnings of emancipatory education. The case study findings, which highlight the stages of the educational program, reveal how young people are empowered to challenge prevailing environments of exclusion and advance practices of positive community social regeneration. The study, thus, provides evidence of a form of education for social transformation (EST) which can contribute meaningfully to a peaceful struggle for social change while simultaneously redefining and humanizing education as a practice of emancipation.